2019
DOI: 10.1002/nafm.10281
|View full text |Cite
|
Sign up to set email alerts
|

Passage Effectiveness at a Pool‐and‐Weir Fishway Designed to Accommodate Pacific Lampreys

Abstract: Providing passage at man‐made barriers is important to preserving migratory fish species. Fishways used to bypass barriers have historically been designed to provide passage for economically important species, with little regard given to nontarget species. Consequently, native fish species whose swimming behaviors are not well suited to these fishways have suffered from restricted access to habitat. For example, poor passage at dams has contributed to declines in populations of Pacific Lamprey Entosphenus trid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Landsman et al, 2018), as well as variants of the Ice‐Harbour design (e.g. Ackerman et al, 2019). Vertical‐slot fishways included any baffled or Hell’s Gate style fishway (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Landsman et al, 2018), as well as variants of the Ice‐Harbour design (e.g. Ackerman et al, 2019). Vertical‐slot fishways included any baffled or Hell’s Gate style fishway (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory experiments indicated that attaching a 0.305-m-wide metal plate over the grating (diffuser plates) allowed lamprey to attach near, and pass through, an orifice opening with > 2.4 m s -1 velocity flow (Daigle et al 2005; Figure 3). In a field study of a pool-and-weir fishway designed to pass lamprey, Ackerman et al (2019) found that with rounded corners with a radius of 1.15 m, flush-mounted weir gates, chamfered corners, and flush orifices, passage efficiency ranged from 84% to 98%. Daigle et al (2005) found that few lampreys passed a weir using the overflow section, although those that did so passed the weir more quickly, in 38 s, than those passing via submerged orifices, averaging 3 m 20 s ( Figure 3).…”
Section: Passage Observations From the Wild And Fishwaysmentioning
confidence: 99%
“…Lampreys, the weakest swimmer reviewed (Figures 1 and 4), typically swim up highvelocity corridors by using their oral discs to attach to suitable substrates in a burst-and-attach behavior. Lamprey-friendly structures need adequate smooth anchorage surfaces and rounded edges with a radius of no less than 0.15 m, to allow them to use their unique burst-andattach behavior (USFWS 2014;Ackerman et al 2019). Lampreys are most vulnerable in the time between successive attachments.…”
Section: Substrates and Surface Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent exception was a new fishway in the Clackamas River (Oregon), where adult Pacific Lamprey behaviors were explicitly considered in the design process, and preliminary passage efficiency estimates were 84–98% (Ackerman et al. ). Low dam passage success has been far more common, however, and has been associated with high water velocity and turbulence in dam tailraces and fishways (Johnson et al.…”
mentioning
confidence: 99%